Using expert judgments to inform economic evaluation of ecosystem-based adaptation decisions: watershed management for enhancing water supply for Tegucigalpa, Honduras - Procter, Amanda (2017)
Acute concerns over the status of ecosystems providing benefits to human communities, and deep uncertainties over the consequences of future climate change, call for new policy choices, as well as improved methods for analysis. This paper considers the profoundly important and under-recognized role of structured judgments provided by technical specialists with local experience in relevant ecological and technological systems, in order to inform climate change adaptation choices, including ecosystem-based adaptation (EBA). It begins with a brief review of the concepts and methods for eliciting judgments from technical experts for complex decisions under uncertainty. Then, the case study is described: an expert judgment task to assess the performance of the recently approved watershed management plan for the Guacerique watershed near Tegucigalpa, Honduras. Several key variables including water yield in dry seasons, cost changes and also more broadly defined ecosystem service benefits, under two climate scenarios, are employed to consider performance. The results provide resource managers with information on how to maximize the adaptation potential of an already approved management plan. It shows that estimates of potential enhanced water flows in dry seasons could yield millions of dollars in annual benefits, based on current water prices paid to informal water suppliers, and depending on future climate scenarios. A broader implication of the study is to document a relatively accessible, cost-effective approach to support policy decisions related to EBA and infrastructure, which is relevant for decisions to help achieve the United Nation’s Sustainable Development Goals.